Concomitant septal myectomy and mitral valve repair in a child with Noonan syndrome. Issue 1 (18th November 2020) - Doi, Toshio; Toritsuka, Daisuke; Higashida, Akihiko; Yokoyama, Shigeki; Fukahara, Kazuaki; Yoshimura, Naoki
Abstract: We successfully performed concomitant septal myectomy and mitral valve repair in a child with Noonan syndrome. Abstract : We successfully performed concomitant septal myectomy and mitral valve repair in a child with Noonan syndrome.